2021
DOI: 10.1111/jfbc.13972
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular mechanisms of genistein in prevention and treatment of diseases: An overview

Abstract: Genistein is the simplest secondary metabolite in soybeans and belongs to a group of compounds called isoflavones. It is a phytoestrogen and it makes up more than 60% of soy isoflavones. Studies have shown the anti‐inflammatory, anti‐apoptotic, and anti‐angiogenic effects of genistein in addition to its modulatory effects on steroidal hormone receptors. In this review, we discuss the pharmacologic and therapeutic effects of genistein on various diseases. Practical applications In this review, we have discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 154 publications
0
21
0
Order By: Relevance
“…Since the consumption of diets high in fats and sugars is also considered a preventable modifiable risk factor, other effective lifestyle alternatives exist for the improvement of brain health. For instance, consumption of plant-based soy-rich foods, including the isoflavone genistein, has been associated with improved cognitive function, cerebral blood flow, and metabolism [ 32 36 ]. Experimentally, genistein has been extensively studied in male and female mice as a promising therapy for the treatment of obesity and diabetes-induced cognitive dysfunction with similar efficacy because of its reported anti-inflammatory, anti-apoptotic, and antioxidant properties [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the consumption of diets high in fats and sugars is also considered a preventable modifiable risk factor, other effective lifestyle alternatives exist for the improvement of brain health. For instance, consumption of plant-based soy-rich foods, including the isoflavone genistein, has been associated with improved cognitive function, cerebral blood flow, and metabolism [ 32 36 ]. Experimentally, genistein has been extensively studied in male and female mice as a promising therapy for the treatment of obesity and diabetes-induced cognitive dysfunction with similar efficacy because of its reported anti-inflammatory, anti-apoptotic, and antioxidant properties [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, consumption of plant-based soy-rich foods, including the isoflavone genistein, has been associated with improved cognitive function, cerebral blood flow, and metabolism [ 32 36 ]. Experimentally, genistein has been extensively studied in male and female mice as a promising therapy for the treatment of obesity and diabetes-induced cognitive dysfunction with similar efficacy because of its reported anti-inflammatory, anti-apoptotic, and antioxidant properties [ 32 ]. In addition, we have recently demonstrated a robust neuroprotective effect of genistein in a model of severe obesity [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological properties of genistein revealed that it has the potential to be a lead molecule in the treatment of a wide range of diseases, including postmenopausal symptoms, cancer, bone, brain, and heart problems [ 10 ]. Since genistein is believed to pass the blood–brain barrier to exert its neuroprotective effect, it is extensively applied in the investigation of the treatment of neurodegenerative diseases, such as Alzheimer’s, Huntington’s, and Sanfilippo disease ( Figure 3 ) [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer is a malignant carcinoma originated from epithelial cells, which is specified by remedial inefficiency and poor diagnosis (1). It is the 4 th cause of death and the 2 nd cause of cancer-related death in the world (2).…”
Section: Introductionmentioning
confidence: 99%
“…Genistein (4' , 7,5-trihydroxyisoflavone) is a phytoestrogen belonging to isoflavones family with ability to inhibit angiogenesis and cell proliferation (1,16). Inhibitory effects of genistein on prostate (12), cervix (17), brain (18), breast (15,19), and colon (13) cancer cell proliferations have been already documented; however, the molecular mechanism of genistein action in gastric cancer has not been explored yet.…”
Section: Introductionmentioning
confidence: 99%